China as aspirant of leader's position in world economy - Báčová, Štěpánka (2012)
This final thesis will be devoted to the position of China in the world economy, and in particular its potential to become the largest economy in the world. High Chinese economic growth of the past ten years, and China's actions have shown its potential to become a world leader. China's competition is current but economically debilitating leader USA. The financial crisis and high debt caused the U.S. economic slowdown and possible potential loss of world leadership. The objective of thesis is to assess, on the basis of the analysis of the current state of the Chinese economy and its growth potential and threats, whether China is to become the world leader in the near future, and takes over that primacy by the longtime leader USA. In order to meet the above mentioned objectives, the thesis also will focus on the current situation of the U. S. economy.